DEMOCRATIZATION OF NATURAL OIL AND GAS NATURAL RESOURCES MANAGEMENT FOR PEOPLE'S WELFARE - Ismail Rumadan (UNTAG Law Review, 2020)
Oil and Gas is one of the natural resources (non-renewable) strategic nonrenewable controlled by the state and a vital commodity that dominate the lives of many people and has an important role in the national economy must be managed optimally provide prosperity and welfare for the people. However, the fact is that oil and gas management has not provided maximum benefit for the welfare of the community's life, due to the management of oil and gas resources which only emphasizes the dredging elementwithout accompanied by protection of community rights as well as countermeasures against the negative impacts of oil and gas activities for the surrounding community. The thing that must be done is to restore the people's sovereignty over oil and gas natural resources by rearranging the management of oil and natural gas by giving more portions to State-Owned Enterprises to manage oil and gas natural resources for the welfare of the people.